if tan A+sin A = m and tan A - sin A = n then prove the following m
![{m}^{2} - {n}^{2} = \sqrt{mn} {m}^{2} - {n}^{2} = \sqrt{mn}](https://tex.z-dn.net/?f=+%7Bm%7D%5E%7B2%7D++-++%7Bn%7D%5E%7B2%7D++%3D++%5Csqrt%7Bmn%7D+)
Answers
Answered by
3
Answer:
your answer attacted in the photo
Attachments:
![](https://hi-static.z-dn.net/files/dbf/ed9be52c541e2f08d84ee23cc025ded1.jpg)
Answered by
2
L.H.S. = ![(tan \: θ + sin θ + tan θ - sin θ ) \\ (tan θ + sin θ - tan θ + sin θ ) (tan \: θ + sin θ + tan θ - sin θ ) \\ (tan θ + sin θ - tan θ + sin θ )](https://tex.z-dn.net/?f=%28tan+%5C%3A+%C2%A0%CE%B8%C2%A0+%2B+sin%C2%A0%CE%B8%C2%A0+%2B+tan%C2%A0%CE%B8%C2%A0+-+sin%C2%A0%CE%B8%C2%A0%29+%5C%5C+%28tan%C2%A0%CE%B8%C2%A0+%2B+sin%C2%A0%CE%B8%C2%A0+-+tan%C2%A0%CE%B8%C2%A0+%2B+sin%C2%A0%CE%B8%C2%A0%29)
Similar questions
Political Science,
4 months ago
Science,
4 months ago
Math,
9 months ago
Math,
1 year ago
Physics,
1 year ago